A novel gas sands characterization and improved depositional modeling of the Cretaceous Sembar Formation, Lower Indus Basin, Pakistan - Aftab, Furqan; Zafar, Mohammad; Hajana, Muhammad Iqbal; Ahmad, Waqar (Frontiers in Earth Science, 2022)
The Lower Indus Basin of Pakistan has substantial hydrocarbon potential with the Cretaceous Sembar Formation as its principal source rock. While studies have identified the shale gas potential of the Sembar Formation, no extensive research has been conducted to evaluate the hydrocarbon potential of thick packages of sands encountered within it. This study is intended to fill this research gap by identifying the hidden-untapped thick packages of sands of the Sembar Formation for the first time in the Khewari and Gambat areas. We use well log and seismic reflection data to define the thickness, depth distribution, and petrophysical properties for reservoir characterization. This integrated modeling identifies favorable zones for gas production and the spatial distribution of sand packages with excellent reservoir properties in thickness (≈200 m), almost continuous sand packages suitable for hydrocarbon exploration. The Suleman-01 well has a very good hydrocarbon reservoir potential with 70% sand volume, approximately 13% effective porosity, 3.57 millidarcys average permeability, and approximately 58–60% hydrocarbon saturation. We suggest that the post-collisional tectonics of the Indian and Eurasian plates affected the depositional geometry of the Sembar Formation in such a way that it trends from shallower to deeper from western to eastern parts of the study area. Similarly, reservoir quality sands follow the positive upward trend from west to east toward the Indian shield. We propose that the approach implemented in this study is applicable to the entire Lower Indus Basin and further toward the Rajasthan Basin in India in the east and Zagros fold-and-thrust belt in Iran in the west. This approach would help assess the undeveloped hydrocarbon potential of the Sembar Formation sands and related formations in South Asia and worldwide.